Cellulose nanocrystal nanocomposites capable of low-temperature and fast self-healing performance. (15th November 2022) - Saddique, Anam; Lee, Hyang Moo; Kim, Jin Chul; Bae, Jinhye; Cheong, In Woo
Abstract: The development of low-temperature self-healing polymers is crucial because high-temperature or softening conditions for rapid self-healing inevitably reduce their mechanical strength. Herein, we first report cellulose nanocrystal (CNC)/polymer nanocomposites with a rapid low-temperature self-healing performance. The nanocomposite was prepared by simple blending of grafted CNC and matrix prepolymer made from the monomers having metal-ligand coordination and lower critical solution temperature functionalities along with the presence of hexamethylene diisocyanate and dibutyltin dilaurate. Owing to the dynamic nature of both hydrogen bonds and metal–ligand coordinated covalent bonds, the resultant nanocomposites showed excellent self-healing efficiency (99 %, within 1 h) at a low temperature (5 °C) with robust mechanical properties including a high stretchability (230 %), high toughness (2538 MJ/m 3 ), enhanced tensile strength (25.49 ± 0.02 MPa), and improved thermomechanical properties. Self-healing performance of the coordinated covalent bonds requiring active hydrogen was considerably improved by the introduction of CNCs with abundant hydrogen bonds. Graphical abstract: Unlabelled Image